2014
DOI: 10.1039/c4cc05215c
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometalated Ir(iii) complexes as targeted theranostic anticancer therapeutics: combining HDAC inhibition with photodynamic therapy

Abstract: The successful design and anticancer mechanistic studies of a series of cyclometalated Ir(III) complexes with histone deacetylase inhibitory and photodynamic therapy (PDT) activities are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(64 citation statements)
references
References 38 publications
(17 reference statements)
4
60
0
Order By: Relevance
“…One study recently reported that HDACis potentiate UVA-mediated phototherapy of T cell lymphoma [35], but UVA itself is known to be a risk factor for cancer [36]. The mechanism of coupling HDAC inhibition to PDT seems to have recently captured the interest of synthetic chemistry wherein two independent studies have each synthesized one new compound possessing both photoactivation and HDAC inhibitory potentials [37, 38]. Combination of PDT with HDAC inhibition represents a novel approach, with potentially promising outcomes, in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study recently reported that HDACis potentiate UVA-mediated phototherapy of T cell lymphoma [35], but UVA itself is known to be a risk factor for cancer [36]. The mechanism of coupling HDAC inhibition to PDT seems to have recently captured the interest of synthetic chemistry wherein two independent studies have each synthesized one new compound possessing both photoactivation and HDAC inhibitory potentials [37, 38]. Combination of PDT with HDAC inhibition represents a novel approach, with potentially promising outcomes, in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we attempted to overcome CRC cell resistance to HY-PDT by pretreatment with HDACis especially that the latter are non-genotoxic agents and can epigenetically sensitize cells to external stimuli. The mechanism of coupling HDAC inhibition to PDT seems to have recently captured the interest of synthetic chemistry wherein two independent studies have each synthesized one new compound possessing both photoactivation and HDAC inhibitory potentials [37, 38]. We tested two chemical groups of HDACis: (a) the hydroxamic acids, which are inhibitors of all classes of HDACs, and (b) the short-chain fatty acids, which are inhibitors of predominantly nuclear HDACs.…”
Section: Methodsmentioning
confidence: 99%
“…1117 The resistance of tumors to platinum decreases the efficacy of platinum-based or even renders them ineffective, causing treatment failure. 1822 In the design of new anticancer drugs, 2329 the ruthenium complexes have raised great interest and have been tested against a number of cancer cell lines, 3036 and are regarded as promising candidates for alternative drugs to cisplatin and its derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cyclometalated Ir(III) complexes are also considered to be potent anticancer candidates as they can target subcellular organelles, inhibit protein activities and act as photodynamic therapeutic agents11121314151617. Our group has endeavored to develop cyclometalated Ir(III) complexes as multifunctional theranostic agents integrating anticancer properties and imaging capabilities14151617.…”
mentioning
confidence: 99%